A fundamental analysis of factors affecting chemical homogeneity in the laser powder bed fusion process. (15th September 2022) - Flint, T.F.; Anderson, M.J.; Akrivos, V.; Roy, M.J.; Francis, J.A.; Vasileiou, A.; Smith, M.C.
Highlights: A high-fidelity Thermal-Fluid Dynamics framework is utilised. The momentum contribution due to condensing vapour bubbles leads to more mixing. Preferential element loss due to heterogeneous boiling of components is quantified. Fundamental insights pertaining to L-PBF of multi-component systems are obtained. Abstract: In this work a novel mathematical framework, that fully describes the fusion and vapourisation state transitions in multi-component systems, has been applied to assist in understanding the fundamental mechanisms of defect formation and chemical homogenisation in the laser powder bed fusion process (L-PBF). Specifically, the role of vapourisation and condensation of the multi-component metallic substrate is investigated to determine the importance of properly capturing the state transitions when understanding the substrate evolution. The framework is applied to a ternary metallic system; it is revealed that entrained vapour bubbles in chemically dissimilar flows promote greater homogenisation during the condensation and collapse of these bubbles when compared to non-condensing phases. It is further shown that as the laser power density is increased, there is a greater tendency for preferential element evaporation of the lighter elements; this preferential element evaporation is quantified numerically for the first time, and shown to be a non-linear function of power density.